A rare cause of sub-acute proximal intestinal obstruction due to annular pancreas in a low-income setting. - Weledji, EP; Ngowe, MN; Mokake, M (Department of Surgery, UKM Medical Centre, 2013)
Annular pancreas (AP) is a rare congenital anomaly due to an abnormal fusion between the tip of the ventral pancreatic bud and the duodenum at about the 7th gestational week and usually presents with symptoms due to duodenal obstruction. We here report a case of a 2-year-old girl who presented for investigations of symptoms of a subacute proximal intestinal obstruction. Investigations revealed a partial duodenal obstruction and an exploratory laparotomy showed a partially obstructing annular pancreas for which she underwent a bypass procedure. A precise preoperative diagnosis of annular pancreas can be difficult without computerized tomography (CT) imaging and the diagnosis and surgical management decision may only be made at laparotomy. Children with atypical or mild symptoms of intestinal obstruction associated with failure to thrive should be investigated fully for a mechanical cause.